Descripción de un caso de diarrea viral bovina (DVB) en la sabana de Bogotá - Mogollón G., José Darío; González, Héctor E.; Cortés C., Esperanza; H. de Galvis, Alba Lucía; Agudelo, Dora Lucia de; Neira, Rafael (Instituto Colombiano Agropecuario - ICA, 2019)
Gross and microscopic lesions of bovine viral diarrhea (BVD) in an eight months old Holstein calf from the Sabana de Bogota are described. The pathological changes consisted of erosions and ulcers in the digestive tract, and fibrinosous membranes and necrosis in the esophagus, small and large intestine. The lesions were similar to those described else where. The diagnosis was confirmed by virus isolation; the ocurrence of this case is discussed in relation with the high serologic prevalence of the disease previously determined.